Integral Study of the Cotton Biocide Plants - Fuertes, César M. (2010)
To study extracts of the cotton biocides it has collected more than thirty species of plants, which were classified taxonomically in the Natural History Museum of the Universidad Nacional Mayor de San Marcos, between species that are considered relevant for its insecticidal properties we have the following species: Tephrosia cinerea (sacha barbasco), Artemisia absinthium (wormwood), Ryania speciosa (riania), Cissampelos grandifolia (legia), Datura stramonium (chamico), Hura crepitans (catahua), Schinus molle (molle), Annona cherimola (chirimoya), Annona muricata (guanabana or graviola), Tagetes patula (Marigold), Tanacetum parthenium (santa maria), Chromolaena laevigata (sacha huaca), Clibadium asperum (huaca), Lonchocarpus nicou (Mount mullein), Lonchocarpus spiciflorus (yumanasa), Centropogon cornutus (arco sacha), Erythrina berteroana (small amasisa), Erythrina edulis (pajuro), Erythrina ulei (amasisa), Melia azedarach (Neem tree) y Agave americana (maguey). Lyophilized extracts were evaluated chemical composition, chromatographic and spectrophotometric profile, their behavior against Artemia salina, biocide bioassays in the laboratory and field level. Among the pests that were investigated are includes: Aphis gossypii, Bemisia tabaci, Dysdercus peruvianus. Extracts of A. americana L., H. crepitants and C. grandifolia showed significant results both at the level of the laboratory and in the cotton crop in the field.